Design, Construction and Performance of an Ohmic Fruit Juice Evaporator - Mohamed Gaily, Mohamed Hassan (1999)
A fruit juice ohmic evaporator (FlOE) was designed and constructed. The design was done in accordance with the basic principle of ohmic heating to provide heat for evaporation instead of steam or conventional direct heating, to overcome problems arising through these methods of heating. The FlOE was constructed mainly from stainless-steel. A cylinderical heating vessel of internal diameter 20.5 cm and length of 3 1 cm was constructed to enclose electrodes supplying the heat for evaporation. The heating vessel was coated internally with epoxy resin to isolate the wall of the vessel from electric current passing through the fluid. Three sets of electrodes connected to the three-phase alternating current supply were used. Each set of electrodes composed of a three parallel stainless-steel plates. A vacuum pump was used to lower the boiling point of the juice below 65°C and as low as 45°C to prevent the nutrient material from damage. Salt-water solution and pineapple juice were used to study the performance of the FlOE. Three types of tests were done. Preliminary tests were conducted to ensure that the FJOE operates within the design limits and to check for fluid and electric leakage. Performance of the FlOE was computed by testing the system in both batch and continuous operation using salt-water solution and pineapple juice. Electric conductivity of the dilute pineapple juice was first measured to find the maximum allowable level of the juice inside the FlOE to prevent current overload or high temperatures during evaporations. Four tests using salt-water solution, two of them in batch mode and two in a continuous mode were conducted. Another four test using pineapple juice of initial concentration of 10% were conducted to achieve a final concentration of 40%, two of them were batch tests and the others in continuous mode operation. Results of all tests were tabulated and illustrated in graphs. Electric current and the total area of electrodes used was found to be the controlling factors during evaporation using the FlOE. Increasing the total contact area between electrodes and the fluid was found to increase the average apparent current and hence the power consumption. Energy cost using the FJOE was found to be relatively cheap and of low cost and the evaporation economy was found to be 0.7. The FlOE was found to be a suitable evaporation equipment for concentrating fruit juices and other food materials in a small scale industries without any need of steam boilers and of low energy cost.